PENGEMBANGAN MEDIA PEMBELAJARAN LEAFLET BERBASIS 3 DIMENSI PADA MATERI ISLAM UNTUK MENDORONG SEMANGAT PESERTA DIDIK - RAHMA DIYAH WERYANI; SUPRIYANTO SUPRIYANTO; SYARIFUDDIN SYARIFUDDIN (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2021)
This study aims to develop and determine the valid 3-dimensional leaflet-based learning media in learning outcomes in History subjects. This development research uses the ADDIE model, where in the ADDIE model there are 5 steps, namely, analysis, design, development, implementation, and evaluation. The subjects of this study were 25 students of class X IPS 1 SMA Negeri 12 Palembang. The validity of the 3-dimensional-based leaflet media has been assessed by 4 experts, namely, 3.88 validity material experts with valid categories, learning design experts 4.73 with valid categories, media experts with 4.21 validity in valid categories, and language experts 4 with valid categories. valid. Overall, this 3-dimensional-based leaflet media has an average value of 4.25 which is included in the valid category. The effectiveness of the 3-dimensional-based leaflet media can be seen from the field test evaluation of 33.38%, so the value obtained from Ngain is 0.56. This shows that the 3-dimensional-based leaflet media with Islamic material on the island of Sumatra shows valid and effective results.